Supporting African American Mothers during Nurse Home Visits in Adopting Safe Sleep Practices. Issue 4 (July 2020) - Stiffler, Deborah; Matemachani, Sherry Mukasa; Crane, Lisa
Abstract: Background: Nurses providing home visits were concerned that some mothers were not routinely using safe sleep practices for their newborns and infants. Purpose: The purpose of this study was to listen to how home visit nurses offer education to their African American clients about the safe to sleep guidelines during the prenatal and postpartum periods and discuss ways nurses could support mothers to be more successful in using safe sleep practices. Study Design and Methods: A focus group was conducted with home visit nurses who partner with pregnant mothers and follow them through the first 2 years of their child's life. We asked the nurses to discuss how they offer information and education to their African American clients about safe sleep practices and what could be done to support adoption of the guidelines. A qualitative narrative approach was used for data analysis. Results: Seventeen home visit nurses participated in the focus group. We identified two overall themes with eight subthemes. The first theme focused on nurses' perceptions about challenges some mothers have in following the recommendations. The second theme included nurses' perspectives on how to better promote the safe sleep message and educating mothers within their cultural context. Clinical Implications: Expectant and new mothers need advice and knowledge about the Safe to Sleep ® guidelines that provide ways to decrease risk of infant death. Nurses must be aware of their clients' culture and beliefs so they can offer support and information on infant safety within that context. Abstract : Sudden unexpected infant deaths are increasing in the United States. In this study, nurses from the Nurse Family Partnership who provide home visits to pregnant women and new mothers in Indiana participated in a focus group to discuss how to better support African American mothers in adopting safe sleep practices that can minimize risk of suddent infant death.